2013
DOI: 10.5897/ajps2013.1077
|View full text |Cite
|
Sign up to set email alerts
|

Studies on floral phenology, fruit and seed maturation and harvest index based on fruit colour in Pongamia pinnata (L.) Pierre

Abstract: Pongamia pinnata is a leguminous tree having enormous potential of producing high seed oil that could be as a source of biofuel. The collection of pods with higher seed quality characters is much important for production of elite seedlings at nursery and hence studies related to seed maturation were initiated as matured seed is the basic character of quality seed. To evaluate the steps in obtaining quality seed from the tree, studies were initiated on floral phenology, fruit and seed maturation and on evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
1
2
0
1
Order By: Relevance
“…Results of research in other commodity showed that there was variation of time Baskorowati et al, 2008). The same result of research was also presented by Srimathi et al (2013) in Pongamia pinnata.…”
Section: Resultssupporting
confidence: 81%
“…Results of research in other commodity showed that there was variation of time Baskorowati et al, 2008). The same result of research was also presented by Srimathi et al (2013) in Pongamia pinnata.…”
Section: Resultssupporting
confidence: 81%
“…In general terms, both fruit and seed must be mature: dryness is indicative of maturation and in this condition they respond favourably to germination (Srimathi et al 2013;Silva et al 2015); in the dehiscent fruits, this is followed by opening, which is an evolutionary characteristic that allows the dispersion of the seeds and occurs when these has dehydrated completely (McAtee et al 2013). In legumes, the process is accompanied by lignification of the fruit covers in order to avoid damaging the seeds with excess moisture and to allow them to maintain dormancy until environmental conditions are favorable (Smýkal et al 2014).…”
Section: Georgina Vargas-simónmentioning
confidence: 99%
“…Because fruits from many forest species change color when they ripen, changes in fruit color have been widely used as the indicator of seed maturity for the harvest of forest seeds (Srimathi et al 2013, Lopes et al 2014, Kaiser et al 2016. In addition to fruit color, other factors such as seed water content and ambient temperature during storage are essential to the maintenance of physiological viability and genetic conservation of plant species, and these factors are frequently the subject of ex situ conservation studies on forest seeds (Borges et al 2009).…”
mentioning
confidence: 99%